EFL STUDENTS' PERCEPTION OF PVN (PERSONAL VOCABULARY NOTES) AS A VOCABULARY LEARNING STRATEGY - Hanifa Aasaa Mufida; Rahayu Kuswardani (SEAMEO QITEP in Language, 2023)
One of the most commonly used vocabulary learning strategies is keeping PVN (Personal Vocabulary Notes). The students apply the PVN strategy to record and organize the words they come across, along with their meanings and any additional information. The primary objective of this study is to find out how students perceive the utilization of the PVN (Personal Vocabulary Notes) as a vocabulary learning strategy based on three components: cognitive, affective, and conative. This study was conducted in a junior high school located in Surabaya. The researchers employed a qualitative descriptive method in this study, which involved nine eighth-grade students in the academic year 2022/2023. The research was carried out in four phases: preliminary study, data collection, data interpretation and analysis, and data presentation. Data was collected through a closed-ended questionnaire consisting of 18 items using a four-point Likert Scale, and a semi-structured interview comprising 9 questions. The research findings from both instruments showed that the majority of students held positive responses. Thus, it can be concluded that EFL students have strongly positive perceptions toward the utilization of PVN as a vocabulary learning strategy to improve vocabulary in terms of cognitive, affective, and conative components.